In Vitro Evaluation of Alpha-Amylase Inhibition and Anti-Glycation Activities of Aloe barbadensis Miller Aqueous Extract (Sahel Journal of Life Sciences FUDMA, 2025)
Postprandial hyperglycemia is largely driven by the rapid enzymatic breakdown of carbohydrates by alpha-amylase, while non-enzymatic protein glycation leads to advanced glycation end products (AGEs) that accelerate diabetic complications. This study investigated the in vitro antidiabetic potential of Aloe barbadensis Miller aqueous extract. The extract was tested for its ability to inhibit alpha-amylase and non-enzymatic haemoglobin glycation. Alpha-amylase inhibition was measured at 0.02-0.08 mg/mL using metformin as the standard, while anti-glycation activity was assessed over the same concentration range using gallic acid as a positive control. Absorbance was measured spectrophotometrically, and percentage inhibition and IC₅₀ values were determined. The extract inhibited alpha-amylase in a concentration-dependent manner, showing 75.53% inhibition at 0.02 mg/mL and 53.67% at 0.08 mg/mL, with an IC₅₀ of 36.59 mg/mL. Metformin produced 87.18% inhibition at 0.02 mg/mL with an IC₅₀ of 0.10 mg/mL. The extract also reduced haemoglobin glycation, producing 51.77% inhibition at 0.02 mg/mL and 41.77% at 0.08 mg/mL, with an IC₅₀ of 0.033 mg/mL, compared to gallic acid’s 36.35% inhibition and 0.0035 mg/mL IC₅₀. Aloe barbadensis aqueous extract exhibited moderate alpha-amylase and anti-glycation activities, supporting its potential as a natural antidiabetic agent. Further studies are needed to isolate its bioactive compounds and confirm their efficacy in vivo.